Characterizing the performance of a POPS miniaturized optical particle counter when operated on a quadcopter drone - Liu, Zixia (2021)
We first validate the performance of the Portable Optical Particle Spectrometer (POPS), a small light-weight and high sensitivity optical particle counter, against a reference scanning mobility particle sizer (SMPS) for a month-long deployment in an environment dominated by biomass burning aerosols. Subsequently, we examine any biases introduced by operating the POPS on a quadcopter drone, a DJI Matrice 200 V2. We report the root mean square difference (RMSD) and mean absolute difference (MAD) in particle number concentrations (PNCs) when mounted on the UAV and operating on the ground and when hovering at 10m. When wind speeds are low (less than 2.6ms-1), we find only modest differences in the RMSDs and MADs of 5% and 3% when operating at 10m altitude. When wind speeds are between 2.6 and 7.7ms-1 the RMSDs and MADs increase to 26.2% and 19.1%, respectively, when operating at 10m altitude. No statistical difference in PNCs was detected when operating on the UAV in either ascent or descent. We also find size distributions of aerosols in the accumulation mode (defined by diameter, d, where 0.1≤d≤1μm) are relatively consistent between measurements at the surface and measurements at 10m altitude, while differences in the coarse mode (here defined by d> 1μm) are universally larger. Our results suggest that the impact of the UAV rotors on the POPS PNCs are small at low wind speeds, but when operating under a higher wind speed of up to 7.6ms-1, larger discrepancies occur. In addition, it appears that the POPS measures sub-micron aerosol particles more accurately than super-micron aerosol particles when airborne on the UAV. These measurements lay the foundations for determining the magnitude of potential errors that might be introduced into measured aerosol particle size distributions and concentrations owing to the turbulence created by the rotors on the UAV.